Experimental analysis of an air cavity concept applied on a ship hull to improve the hull resistance. (1st December 2015) - Butterworth, Jamie; Atlar, Mehmet; Shi, Weichao
Abstract: At the forefront of ship design is the desire to reduce a ship׳s resistance, thus being the most effective way to reduce operating costs and fulfil the international criteria for reduction in CO2 emissions. Frictional drag is always proportional to the wetted surface of the vessel and typically accounts for more than 60% of the required propulsive power to overcome; hence the desire to reduce the wetted surface area is an active research interest. An initial full-scale sea trail on a vessel by introducing air as a lubricating medium has indicated 5–20% propulsive energy savings (DK-GROUP, 2010 ). Following the report of the fundamental tests with the air cavity concept applied on a flat plate, which was conducted in the Emerson Cavitation Tunnel of Newcastle University (Slyozkin et al., 2014 ), this paper explores the same concept only this time applied on an existing container ship model to investigate whether it benefits in frictional drag reduction, whilst producing a net energy saving. The middle section of this 2.2 m ship model was modified to accommodate a 0.43×0.09 m 2 air cavity in the bottom of the hull and then various model scale tests have been conducted in the towing tank of Newcastle University. The model experiments produced results ranging from 4% to 16% gross drag reduction. Upon applying scaling factors, it is estimated from the experimental results that around 22% gross energy could be saved in a full-scale application with just a 5% reduction in the wetted surface area. Further complementary model tests were also conducted to explore the effect of the air cavity on the stability of the model and on the vertical motion responses in a regular head and following wave. While the cavity did not affect the vessel stability the motion response behaviour seemed to be affected non-linearly by the effect of the air cavity. Highlights: An air cavity concept is applied on a container ship model to investigate whether it benefits in frictional drag reduction. The model experiments produce results ranging from 4% to 16% gross drag reduction. 22% gross energy could be saved in a full-scale application with just a 5% reduction in wetted surface area. From the inclination tests, the cavity did not affect the vessel stability. Seakeeping test shows that the vertical motion responses of the hull are affected non-linearly by the air cavity.